The Effect Of Drying Temperature On The Quality Of Ginger Jelly Candy - Sari, Fauziah Novita; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
Jelly candy is an intermediate moisture food product. Drying jelly candy usually uses sunlight, but if the weather is cloudy or even rainy, the drying process cannot be carried out. Therefore, drying is done with the help of a mechanical device, namely a food dehydrator. The use of a food dehydrator is an alternative that can be used in the drying process. This study aims to determine the effect of drying temperature (55°C, 65°C, and 75°C) on the quality of ginger jelly candy and also to determine the right drying temperature to produce ginger jelly candy with the best quality. This type of research is a pure experiment with a completely randomized design (CRD). The data used is primary data obtained directly from 5 expert panelists who provide answers from a questionnaire (organoleptic test format) on the quality of ginger jelly candy. The data that has been obtained is then tabulated in the form of a table and an Analysis of Variance (ANOVA) is performed. If the analysis of variance shows Fcount Ftable, then it is continued with Duncan's test. The results showed that there was a significant effect of different drying temperatures on the quality of color, texture, and taste of ginger jelly candy. The results of the quality test of ginger jelly candy with different drying temperatures were the best at treatment X2 of 65°C.